Midlevel Providers in Orthopaedic Surgery: The Patient’s Perspective - Manning, Blaine T. (Iowa Orthop J, 2019)
BACKGROUND: Midlevel providers (i.e. physician assistants [PAs] and nurse practitioners [NPs]) are being integrated into systems of care due to the exponentially increasing demand for orthopaedic care. There is a lack of studies which investigate orthopaedic patients’ perspectives regarding midlevel providers. METHODS: An anonymous questionnaire was administered to 538 first-time patients of four orthopaedic surgeons before their new patient visit. Content included patient perspectives regarding: optimal scope of practice, midlevel provider importance in physician selection, and reimbursement equity with physicians. RESULTS: Of 538 consecutive patients, 415 (77%) responded. 57% were female with an average age of 63.9 ± 11.4 years. Most patients (68%) considered the training background of the surgeon’s midlevel provider when initially choosing an orthopaedic surgeon. 34% of all patients perceived PAs to be more highly trained than NPs while 17% perceived the opposite. Patients had specific preferences regarding which services should be surgeon-provided: follow-up for abnormal tests (82%), initial postoperative appointment (81%), new patient visits (81%), and determining the need for advanced diagnostic studies (e.g. MRI) (76%). Patients had specific preferences regarding which services could be midlevel-provided: preoperative teaching (73%), minor in-office procedures (65%), long term postoperative appointments (61%), and prescriptions (61%). Patients lacked a consensus on reimbursement equity for midlevel providers and orthopaedic surgeons, despite most patients (78%) reporting the surgeon provides a higher-quality consultation. CONCLUSIONS: As health care becomes increasingly consumer-centric and value-driven, a databased utilization of midlevel staff will allow orthopaedic physicians to optimize efficiency and patient satisfaction. Surgeons may consider our results in division of clinical duties among midlevel staff since patients had specific preferences regarding which services should be physician-provided or midlevel-provided. Orthopaedic surgeons may also consider including the midlevel provider in marketing efforts, as most patients considered the midlevel provider’s training background when initially choosing a surgeon and perceived PAs to be more highly trained than NPs. Patients lacked a consensus towards reimbursement equity for orthopaedic surgeons and midlevels, despite reporting that the surgeon provides a higher quality consultation. These findings are important as the midlevel workforce grows in response to the rising demand for orthopaedic care. Level of Evidence: IV